ISI PESAN DAKWAH AQIDAH DAN SYARIAH DALAM FILM INDONESIA ISLAMI “JILBAB TRAVELER LOVE SPARKS IN KOREA”: Kajian Semiotik pada Film Islami Indonesia - Masturina Khoirun Nisa; Ucik Ana Fardila; Agus widodo (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2019)
This research purposed to determine the preaching messages of aqeeda and sharia in the movie "Jilbab Traveler Love Spark in Korea". The methode of the research used qualitative approachment of Ferdinand de Saussure semiotic analysis to determine the meanings of every adegans, texts, sounds, dialogues, sounds, videos and symbols in the movie. The results of this research showed that there are preaching messages of tafakkur, istighfar, and dzikr in the movie. The preaching messages in sharia aspects are praying, dresses, fasting, sadaka, sincerity (ikhlas) attitude, obidient to alcohols and porks prohibition. The preaching messages in muamalat aspects are obidient to Islam’s law, discussing polygamy issues and to follow premarital process of Islam before marriage (khitba and taaruf).